Incidence of elongated styloid process: A radiographic study - Tushar Phulambrikar; A Rajeshwari; B Balaji Rao; Ashish M Warhekar; Prashanthi Reddy (Wolters Kluwer Medknow Publications, 2011)
Many studies revealed that the styloid process and the stylohyoid chain presented considerable anatomic variability. Many times this elongated styloid process has also been attributed as a cause of pain and discomfort in the neck and throat region which was known as Eagle's syndrome or styloid syndrome or stylohyoid syndrome. Hence, a study was designed to determine the length of styloid process on the orthopantomograph and review the selected related literature. A total of 200 healthy subjects of both the sexes in the age group of 5 to 75 years were radiographed. Each styloid process form both sides was classified to its morphologic appearance and measured. The data was subjected to statistical analysis which revealed elongation of styloid process increases as the age advances, when the incidence of elongation is compared on the right and left side no statistically significant difference is found. Pain is not associated with length or incidence of elongation.